Assessment of premature mortality for noncommunicable diseases - Plinio Tadeu Istilli; Carla Regina de Souza Teixeira; Maria Lúcia Zanetti; Rafael Aparecido Dias Lima; Marta Cristiane Alves Pereira; Waleska Zafred Ricci (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze premature mortality and Potential Years of Life Lost by noncommunicable diseases in a city in the countryside of São Paulo from 2010 to 2014. Methods: ecological study of temporal tendency, using secondary source. For analysis, the premature mortality coefficient and the Potential Years of Life Lost indicator were used. Results: males had the highest premature mortality rate due to cardiovascular disease, with 213.04 deaths per 100 thousand inhabitants, followed by neoplasms, with 188.44. In women, there was an inversion with 134.22 deaths from cancer and 110.71 deaths from cardiovascular disease. Regarding Potential Years of Life Lost, males had an average of 12.19 years lost by death and females of 13.45 years lost. Conclusions: the results reinforce the need to increase public health prevention and promotion policies to reduce premature deaths, especially among men.